BIO - MEDICAL SUBJECTS TEACHING IN PREPARATION OF PHYSICAL EDUCATION PEDAGOGUES (Fiep Bulletin - online, 2014)
The process of biological and medical subjects teaching at Comenius University - Faculty of physical education and sports in Bratislava – Slovakia was analyzed in terms of quality and quantity. We compared the number of subjects, the number of lessons well as the number of credits (expressing the difficulty of individual subjects) with prior periods as well as with the state in certain surrounding countries. According to the results of questionnaire most students find Anatomy, Functional anatomy and Physiology very important subjects and the number of credits of all subjects sufficient. Half of students think that the number of lessons is too low (except of Biochemistry). Physiology is considered to be most interesting and Anatomy most difficult subject. Most students admit that they devote little time to the preparation of the bio-medical subjects. Acknowledgment: The research was supported by VE GA grant 1/1045/12.
Keywords: physical education and sports; biological and medical subjects